Experimental study of the flux trap effect in a sub-critical assembly - Routsonis, K.; Stoulos, S.; Clouvas, A.; Varvayanni, M.; Catsaros, N.; Manolopoulou, M. (HNPS Advances in Nuclear Physics, 2019)
The neutron flux trap effect was experimentally studied in the sub-critical assembly of the Atomic and Nuclear Physics Laboratory of the Aristotle University of Thessaloniki, using delayed gamma neutron activation analysis (DGNAA). Measurements were taken within the fuel grid, in vertical levels symmetrical to the Am-Be neutron source, before and after the removal of fuel elements, also permitting a basic study of the vertical flux profile. Three identical flux traps of diamond shape and an area of 96 cm2 were created by removing four fuel rods for each one. Two (n,γ) reactions and one (n,p) threshold reaction were selected for thermal, epithermal and fast flux study. For the thermal and epithermal flux, results obtained through the 197Au(n,γ)198Au, and 186W(n,γ)187W reactions were used, with and without Cd covers, to differentiate between the two flux regions. For the fast flux, the 58Ni(n,p)58Co reaction was used. All measurements were taken in a HPGe detector of 42% relative efficiency, with a resolution of 1.8 keV at 1332 keV and analyzed in the SPECTRW software package, developed at NCSR Demokritos. An interpolation technique based on local procedures is used to fit the cross sections and the flux spectra. End results show a thermal flux increase of 105% at the source level, and 90% across all levels, pointing to a high potential to increase the available thermal flux for future experiments. Furthermore, the vertical flux profile was found to be slightly asymmetric, with higher flux values at the top part of the assembly.